Exhibitionism - a review of research - Wdowiak, Krystian; Maciocha, Agnieszka; Wąż, Julia; Witas, Aleksandra; Drogoń, Justyna; Chachaj, Weronika; Słomka, Paulina; Gardocka, Ewa (Journal of Education, Health and Sport, 2025)
Introduction and Objective: Exhibitionism is a paraphilic behavior characterized by a persistent or recurrent tendency to expose one’s genitalia to strangers, typically without the intention of further interaction. The aim of this publication is to discuss various aspects of exhibitionism based on the latest literature. Review Methods: A search was conducted in the PubMed database to identify scientific articles containing the term “exhibitionism” in their title, abstract, or keywords. The search focused on articles published between 2014 and 2024, with an emphasis on studies exploring the etiology, prevalence, and treatment of exhibitionism. Brief Description of the State of Knowledge: While often linked to sexual excitement and followed by masturbation, exibitionism is more commonly observed in men. Research highlights several potential risk factors for exhibitionistic disorder, including childhood sexual or emotional abuse, hypersexuality, and sexual preoccupation. Neurobiological, cognitive, and social mechanisms are believed to underlie the development of these tendencies. Treatment of exhibitionistic disorder primarily involves cognitive behavioral therapy (CBT). Pharmacological approaches are also employed to manage symptoms by modulating serotonergic transmission. Summary: Although relatively uncommon, exhibitionistic disorder has significant implications for individuals and society, underscoring the need for improved awareness, accurate prevalence estimates, and expanded access to effective treatment interventions. Further investigation into the true prevalence of exhibitionistic disorder is warranted, as current estimates may be imprecise.